Bimetallic plasmonic Au@Ag nanocuboids for rapid and sensitive detection of phthalate plasticizers with label-free surface-enhanced Raman spectroscopy. Issue 12 (17th May 2019) - Hu, Xiaoyan; Wang, Xinru; Ge, Zipan; Zhang, Le; Zhou, Yaru; Li, Jingya; Bu, Linfeng; Wu, Hengan; Li, Pan; Xu, Weiping
Abstract : Phthalate plasticizers (PAEs) are posing a serious threat to human health, so it is urgent to develop effective and reliable ways to detect the food additives PAEs sensitively. Abstract : Phthalate plasticizers (PAEs) are posing a serious threat to human health, so it is urgent to develop effective and reliable ways to detect the food additives PAEs sensitively. In this study, we have reported plasmonic bimetallic Au@Ag core–shell nanocuboids for the rapid and sensitive detection of PAEs in liquor samples with a label-free Surface-enhanced Raman Spectroscopy (SERS) strategy. Compared with single-element nanostructures, the bimetallic SERS platform can integrate two distinct functions into a single entity with unprecedented properties. Consequently, we synthesized Au@Ag nanocuboids (Au@Ag NCs) composed of a Au nanorod (Au NR) core and a Ag cuboid shell, which could produce richer and broader plasmonic resonance modes than Au NRs. It is obvious that the SERS signals of crystal violet (CV) and butyl benzyl phthalate (BBP) reached a maximum as the thickness of the Ag coating shell was in a certain threshold and there was a strong dependence of the Raman enhancement on the Ag cuboid shell-thickness. Based on the optimized size, the sensitivity and repeatability of Au@Ag NCs were evaluated with limits of detection (LODs) at around 10 −9 M both for BBP and diethylhexyl phthalate (DEHP). In addition, the SERS active substrate core–shell Au@Ag NCs can be used to detect BBP as low as 1.3 mg kg −1 spiked into the liquor samples. Thereby, the unique bimetallic Au@Ag NCs showed a huge potential for the rapid and sensitive detection of PAEs in liquor samples.